2015
DOI: 10.1016/j.bmc.2015.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial benzoheterocyclic 4-aminoquinolines: Structure–activity relationship, in vivo evaluation, mechanistic and bioactivation studies

Abstract: A novel class of benzoheterocyclic analogues of amodiaquine designed to avoid toxic reactive metabolite formation was synthesized and evaluated for antiplasmodial activity against K1 (multidrug resistant) and NF54 (sensitive) strains of the malaria parasite Plasmodium falciparum. Structure-activity relationship studies led to the identification of highly promising analogs, the most potent of which had IC50s in the nanomolar range against both strains. The compounds further demonstrated good in vitro microsomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…33, 35 The relationship was statistically significant with P < 0.0001. Furthermore, a moderately good r 2 value of 0.68 was observed for the correlation, which increased to r 2 = 0.84 upon removal of the point corresponding to compound 15i , which was an apparent outlier (Figure 7b).…”
Section: Resultsmentioning
confidence: 82%
“…33, 35 The relationship was statistically significant with P < 0.0001. Furthermore, a moderately good r 2 value of 0.68 was observed for the correlation, which increased to r 2 = 0.84 upon removal of the point corresponding to compound 15i , which was an apparent outlier (Figure 7b).…”
Section: Resultsmentioning
confidence: 82%
“…Studies have shown that compounds with piperidine rings [4,8,[21][22][23][24][25][26] have good selectivity and activity for the P. falciparum strain. This prompted us to assess their antiplasmodial activity against the chloroquine-sensitive 3D7 and chloroquine-resistant W2 strains of P. falciparum as well as their cytotoxic activity against HUVEC cells (Tables 3 and 4).…”
Section: The Antimalarial Activity Of Derivatives 6 and Target Compoumentioning
confidence: 99%
“…The 4-arylaminopiperidine is a structural moiety found in many alkaloids [4][5][6][7][8][9][10][11] and pharmaceutical products such as fentanyl and structurally-related analgesic opioids or H1-antihistamines agents such as bamipine [12][13][14][15][16][17] and neurokinin 1 (NK1) receptor antagonists [18][19][20]. Studies have shown that compounds with piperidine rings [4,8,[21][22][23][24][25][26] have good selectivity and activity for the P. falciparum strain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations